Розробка рекомендаційної системи вибору органічної продукції - Кастиркін, Д. Р. (ХНУРЕ, 2024)
Іn modern e-commerce, the focus extends beyond merely selling products; it entails employing strategies to stimulate increased customer engagement and purchases. Personalized recommendations serve as a pivotal tool enabling businesses to anticipate customer preferences and behaviors regarding their organic product offerings on web platforms or mobile applications. These recommendations convey the affinity or relevance between objects, exemplified by user ratings or bookmarked pages, thus enhancing the overall user experience and driving sales.
Keywords: рекомендаційна система; органічна продукція